Vocal repertoire of wild blonde capuchins (Sapajus flavius) and contextual use of calls. Issue 6 (2nd March 2015) - Bastos, Monique; Souto, Antonio; Jones, Gareth; Eason, Perri; Bione, Camila; Schiel, Nicola; Bezerra, Bruna
<x xml:space="preserve">Abstract</x> Despite advances in the study of capuchin monkeys (Cebus and Sapajus), there is fairly limited information on their vocal communication systems. The present study focused on investigating the structure and use of vocalizations by wild blonde capuchin monkeys, Sapajus flavius. The study subjects produced 29 different call types, which we grouped into 10 categories according to their behavioral context. The number of call types per context varied from one to six. Some of the call types in the vocal repertoire were only produced by individuals of specific age classes. The "nhan" call, for instance, was only emitted by infants, whereas the "ghrr" call was specific to adults. Other call types had no age‐specificity and were produced by animals of two or more age categories. Discriminant Function Analysis correctly classified 77.4% of calls to type (n = 14 types). The "huh" and "huh‐1var" calls, which are food‐associated calls, were most commonly used, together representing approximately 52% of recorded vocalizations. Information on the vocal repertoire of blonde capuchins increases our knowledge of this very little known and Critically Endangered species. Ultimately, it may be used as a tool to help survey these animals in the wild and to assess welfare in captivity. Am. J. Primatol. 77:605–617, 2015. © 2015 Wiley Periodicals, Inc.